Further Biochemical Profiling of Hypholoma fasciculare Metabolome Reveals Its Chemogenetic Diversity - Al-Salihi, Suhad A. A.; Bull, Ian D.; Al-Salhi, Raghad; Gates, Paul J.; Salih, Kifah S. M.; Bailey, Andy M.; Foster, Gary D. (Frontiers in Bioengineering and Biotechnology, 2021)
Abstract There is a desperate need in continuing the search for natural products with novel mechanism to battle the constant increase of microbial drug resistance. Previously mushroom forming fungi were neglected as a source of novel antibiotics, due to the difficulties associated with their culture preparation and genetic tractability. However, modern fungal molecular and synthetic biology tools, renewed the interest in exploring mushroom fungi for novel therapeutics. The aim of this study was to have a comprehensive picture of nine basidiomycetes secondary metabolites (SM), screen their biological and chemical properties to describe the genetic pathways associated with their production. H. fasciculare revealed to be highly active antagonistic species, with antimicrobial activity against three different microorganisms -Bacillus subtilis, Escherichia coli and Saccharomyces cerevisiae-. Extensive genomic comparison and chemical analysis using analytical chromatography, led to the characterisation of more than 15 variant biosynthetic gene clusters and the first identification of a potent antibacterial metabolite- 3, 5-dichloromethoxy benzoic acid (3, 5-D)- in this species, for which a biosynthetic gene cluster was predicted. This work demonstrates the great potential of mushroom forming fungi as a reservoir of bioactive natural products which are currently unexplored, and that access to their genomic data and structural diversity natural products via utilizing modern computational analysis and efficient chemical methods, could accelerate the development and applications of such distinct molecules in both pharmaceutical and agrochemical industry.